Gender, "the Body" and "Prestigious Imitation" in the Brazilian Culture - Goldenberg, Mirian (Saúde e Sociedade, 2011)
In this text I discuss the role of the body as an important form of physical, symbolic, and social capital in the Brazilian culture. I try to show the distinguishing traits of a culture in which the body is a crucial element in the construction of a national identity by calling forth the ideas of the Brazilian anthropologist Gilberto Freyre and the French anthropologists Marcel Mauss and Pierre Bourdieu. "The body" is a capital in the universe I have researched, a distinctive body which synthesizes three interrelated concepts: 1) the body as insignia (or emblem) of the effort each one has made to control, imprison, and domesticate the body in order to achieve "good shape"; 2) the body as a fashion icon (or brand), which symbolizes the superiority of those who possess it; and 3) the body as a prize (medal), deservedly earned by those who were able to achieve a more "civilized" physique through their hard work and sacrifice. It can be said that in Brazil the body is a capital, maybe the most desired one by the urban middle class and also by lower strata, which perceive the body as a fundamental vehicle for social ascension, and also an important form of capital in the job, spousal, and erotic markets.